The AAMC Standardized Video Interview: Reactions and Use by Residency Programs During the 2018 Application Cycle. (October 2019) - Gallahue, Fiona E.; Hiller, Katherine M.; Bird, Steven B.; Calderone Haas, Mary Rose; Deiorio, Nicole M.; Hern, H. Gene; Jarou, Zachary J.; Pierce, Ava; Geiger, Thomas; Fletcher, Laura
Abstract : Purpose: To evaluate how emergency medicine residency programs perceived and used Association of American Medical Colleges (AAMC) Standardized Video Interview (SVI) total scores and videos during the Electronic Residency Application Service 2018 cycle. Method: Study 1 (November 2017) used a program director survey to evaluate user reactions to the SVI following the first year of operational use. Study 2 (January 2018) analyzed program usage of SVI video responses using data collected through the AAMC Program Director's Workstation. Results: Results from the survey (125/175 programs; 71% response rate) and video usage analysis suggested programs viewed videos out of curiosity and to understand the range of SVI total scores. Programs were more likely to view videos for attendees of U.S. MD-granting medical schools and applicants with higher United States Medical Licensing Examination Step 1 scores, but there were no differences by gender or race/ethnicity. More than half of programs that did not use SVI total scores in their selection processes were unsure of how to incorporate them (36/58; 62%) and wanted additional research on utility (33/58; 57%). More than half of programs indicated being at least somewhat likely to use SVI total scores (55/97; 57%) and videos (52/99; 53%) in the future. Conclusions: Program reactions on the utility and ease of use of SVI total scores were mixed. Survey results indicate programs used the SVI cautiously in their selection processes, consistent with AAMC recommendations. Future user surveys will help the AAMC gauge improvements in user acceptance and familiarity with the SVI. Abstract : Supplemental Digital Content is available in the text.